PERJUMPAAN ETIS DENGAN WAJAH YANG-LAIN: MEMBACA KARYA SASTRA DENGAN “ETIKA” LEVINASIAN - Achmad Fawaid (POETIKA, 2013)
This paper aims to introduce a theoretical approach to literary studies regarding with relation between ethics and literature. For this pur pose, an ethical encounter, flourished by Emmanuel Levinas, will be highlighted to figure out that relation within Danarto and Putu Wijaya‘s narratives. The philosophical research is a kind of  methodology on which this paper is based in order to search a possible way of  adopting Levinasian ethics as method of  literary analysis. It has resulted in some initial findings: (1) Danarto and Putu Wijaya‘s narratives can be regarded as ones conceiving ethical dimension and (2) some implications emerge subsequent to the analysis of  relationship between Levinasian ethics and literature.Keywords: relation, ethics, literature, Levinas, Danarto and Putu Wijaya